2017
DOI: 10.1016/j.msea.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment and its sequence on elevated-temperature properties of Al-Mn-Mg 3004 alloy

Abstract: Various heat treatments with different sequences between the peak precipitation treatment (375°C/48h, referred to as "P") and the high temperature treatment (450-600 °C, referred to as "H") were performed in Al-Mn-Mg 3004 alloys to simulate their thermal treatments during thermomechanical fabrication processes in the present work. Their influences on the dispersoid precipitation and elevated-temperature properties (yield strength and creep resistance at 300 °C) were investigated. The results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For Alloy B (0.5% Mn), the highest value of YS is 55 MPa at 400 ℃/2 h and 450 ℃/2 h. For Alloy C (1%Mn), the highest YS is 70 MPa under 350 ℃/24 h and 400 ℃/2 h conditions compared to 30 and 28 MPa for Alloy A under such conditions, which represents a more than 130% improvement in the YS at 300 ℃, confirming the essential contribution of the precipitation of dispersoids on the elevated-temperature strength [14] . With the increasing heat treatment temperature, a gradual decrease in YS is observed for Alloy C at 450 ℃/2 h and 450 ℃/16 h, whereas the YS of Alloy B decreases slightly at 450 ℃/16 h due to the coarsening of dispersoids at high temperature [5,23] . On the other hand, the difference in YS between Alloy B and Alloy C also changes with the precipitation treatment conditions.…”
Section: Elevated-temperature Strength and Thermal Stability Of Dispe...mentioning
confidence: 99%
“…For Alloy B (0.5% Mn), the highest value of YS is 55 MPa at 400 ℃/2 h and 450 ℃/2 h. For Alloy C (1%Mn), the highest YS is 70 MPa under 350 ℃/24 h and 400 ℃/2 h conditions compared to 30 and 28 MPa for Alloy A under such conditions, which represents a more than 130% improvement in the YS at 300 ℃, confirming the essential contribution of the precipitation of dispersoids on the elevated-temperature strength [14] . With the increasing heat treatment temperature, a gradual decrease in YS is observed for Alloy C at 450 ℃/2 h and 450 ℃/16 h, whereas the YS of Alloy B decreases slightly at 450 ℃/16 h due to the coarsening of dispersoids at high temperature [5,23] . On the other hand, the difference in YS between Alloy B and Alloy C also changes with the precipitation treatment conditions.…”
Section: Elevated-temperature Strength and Thermal Stability Of Dispe...mentioning
confidence: 99%
“…It is reported that the yield strength of 3003 at room temperature (RT) after 375°C/24h has been improved to 80 MPa compared with 52MPa after 600°C/24h due to precipitation of dispersoids [7]. Recently, present authors have systematically studied the evolution of dispersoids at relative lower heat treatment temperature (300-425°C) and their influence on elevated-temperature properties in AlMn-Mg 3004 alloys [6,[8][9][10][11][12]. It is found that high volume fraction and well distributed α-Al(MnFe)Si dispersoids are observed after treated at 375°C for 48h, leading to the remarkable improved YS and creep resistance at elevated-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…With a comparable thermal stability to the expensive Sc-containing dispersoids, the nano-sized Mn(Fe)-containing dispersoids have the potential to be developed as a cheaper solution for designing high-temperature Al alloys [17,18]. AA3xxx and some Mn-containing 5xxx and 6xxx Al alloys are normally supersaturated with Mn in the as-cast state [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the dispersion hardening effect of Mn(Fe)-containing dispersoids has been re-assessed. It is found that a proper heat treatment can produce a higher number density of nano-sized α-Al(Mn,Fe)Si dispersoids and therefore a significant dispersion hardening [17][18][19]27,[33][34][35]. For example, by an isothermal annealing at 375 °C for 24 h, the yield strength of AA3003 alloy could be increased by 53.8% in comparison to the as-homogenized sample (600 °C, 24 h) [19].…”
Section: Introductionmentioning
confidence: 99%